The Decline of International Law as a Normative Ideal - Scott, Shirley V (Victoria University of Wellington Law Review, 2018)
International law was integral to the rise in power of the United States and has been central to the operation of world politics during the period in which the United States has been the dominant state. This article draws on the theory of International Law as Ideology to explain the manner in which the ideal of international law as politically neutral has served as a rhetorical fulcrum. The theory also offers a framework within which to perceive and assess the significance of an apparent sidelining of the ideal in global politics, including, notably, by the United States. While reduced use of the ideology of international law and introduction of the term "rules-based international order" or "rules-based order" might be the best strategic option at a time of declining power, the theory of International Law as Ideology illuminates the manner in which these developments may at the same time be unwittingly contributing to that decline.